The Enrichment of the Vocabulary of Modern Eastern Armenian according to the words not found in "New Haikazian Language Dictionary" - Paronyan, Naira; Grigoryan, Susanna (Bulletin of Yerevan University B: Philology, 2024)
The present work aims to show the enrichment of the vocabulary of Modern Eastern Armenian according to the words not found in the "New Haikazian Language Dictionary". As it is known, the most sensitive of the components of the language is its vocabulary, directly expressing the changes in social life. The vocabulary of the Armenian language has been constantly changed, supplemented with numerous new words and combinations, which need a thorough examination. Some words have survived to this day and kept their basic meanings. Some have survived but have acquired new meanings. We have tried to demonstrate the shifts and changes made in Grabar vocabulary, and some lexical peculiarities, by comparing the word material attested in L. Hovhannisyan’s "Grabar dictionary, words not attested in New Haikazian dictionary" and the above-mentioned dictionaries of Modern Armenian. The wealth of each language is determined by the wealth of its vocabulary, which includes various word layers, distinguished by their word products and functions, and form independent groups. We have singled out words belonging to different semantic fields, and performed their examination, presenting the etymology of root words included in those semantic fields. Based on the statistical data of the dictionaries, it becomes clear that some words included in different thematic groups, which are recorded as lexical units in the dictionaries, stand out for their passive use, are not functionally viable, are inferior to others in terms of application and quantity, but it is not excluded that they can further add to the vibrant vocabulary of the language.